2012
DOI: 10.4194/1303-2712-v12_3_04
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Brown trout Salmo trutta (~1 g) were fed four casein-gelatin based diets with different lipid resources for 6 weeks. The sources of dietary lipid were menhaden oil (MO diet), hazelnut oil (HO diet,), a blend of linseed oil and soybean oil (1:1) (LO+SO diet), and soybean lecithin (LE diet). Feeding trial was conducted in a recirculating water system at 13±0.2°C. Fish fed LO+SO diet demonstrated the highest growth performance while those fed HO diet had the lowest growth rate (P<0.05). The fatty acid profiles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…A similar result was obtained by Kutluyer et al (2017). In a previous study, Arslan et al (2012) found that Brown trout (Salmo trutta) fed with diets including a blend of soybean and linseed oils for 6 weeks had the greatest growth performance. The 30 th day results of our study were similar to the results of Arslan et al (2012), but after the 60 th day of trial, the difference between the FO and 50-50SO-LO diet groups became insignificant.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A similar result was obtained by Kutluyer et al (2017). In a previous study, Arslan et al (2012) found that Brown trout (Salmo trutta) fed with diets including a blend of soybean and linseed oils for 6 weeks had the greatest growth performance. The 30 th day results of our study were similar to the results of Arslan et al (2012), but after the 60 th day of trial, the difference between the FO and 50-50SO-LO diet groups became insignificant.…”
Section: Discussionsupporting
confidence: 69%
“…In a previous study, Arslan et al (2012) found that Brown trout (Salmo trutta) fed with diets including a blend of soybean and linseed oils for 6 weeks had the greatest growth performance. The 30 th day results of our study were similar to the results of Arslan et al (2012), but after the 60 th day of trial, the difference between the FO and 50-50SO-LO diet groups became insignificant. In an other study, Aminikhoei et al (2013) found no significant differences in growth performance of juvenile rockfish (Sebastes schlegeli) fed with diets containing either fish oil, soybean oil, linseed oil, or a mixture of SO and LO for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, although there was no significant difference between the TL values of the two treatments after 30 days, the Nile tilapias fed with the supplemented diet (TII) grew more and gained more weight to those fed with the control diet (TI). Arslan et al 48 and Montanher et al 37 also reported this behavior, i.e., the fish preference for diets supplemented with LNA.…”
Section: Growth Weight Gain and Total Lipids Of Nile Tilapiamentioning
confidence: 95%
“…Brown trout can be considered as an important fish species in Turkey. It is highly accepted in Turkey and the local market value is higher than rainbow trout (Arslan, Sirkecioglu, Bayir, Arslan, & Aras 2012). Europe and Turkey are the natural distribution area of brown trout (Yeşilayer & Genç, 2013).…”
Section: Sample Collectionmentioning
confidence: 99%